Dental undergraduate students’ knowledge attitudes and practices in oral health selfcare: A survey from a South African university - Shenuka Singh; Sudharani Pottapinjara (South African Medical Association, 2017)
Background. Dental students are seen as role-models for promoting good oral health behaviour, yet there is little published evidence in South Africa (SA) that describes student knowledge and attitudes towards their own oral healthcare.Objective. To investigate undergraduate dental therapy and oral hygiene students’ knowledge and attitudes towards their self-care practices and the perceived influence of the dental curriculum on these practices.Methods. This was a descriptive survey of 64 undergraduate dental students at the University of KwaZulu-Natal, Durban, SA. A self-administered questionnaire was used for data collection.Results. Fifty-two respondents returned the completed questionnaires, yielding an 81% response rate. Almost all respondents (n=30; 96.8% (2nd-year students), and n=21; 100% (3rd-year students)) indicated the use of toothpaste and toothbrush to clean their teeth. Most respondents reported cleaning their teeth from 1 to 5 minutes, with 52% (n=27) reporting 1 - 2 minutes and 42% (n=22) 3 - 5 minutes. Only three respondents reported cleaning their teeth for >5 minutes (n=3; 6%). Other practices included the use of toothpicks (n=12; 23%), dental floss (n=42; 81%), and interdental brushes (n=5; 10%). Almost all respondents (n=50; 96%) indicated the use of commercially available mouth rinses. All 2nd-year students (n=30) and 90% of 3rd-year students (n=18) agreed that exposure to clinical training increased their awareness of self-care practices.Conclusion. Respondents reported good knowledge and practice of oral health self-care, but there were inconsistencies in these practices. Respondents also agreed that the dental undergraduate curriculum did influence their knowledge and oral health self-care practices.